Field experiments and main understanding of shale oil hydraulic fracturing - Zhao, Mengyun (Frontiers in Earth Science, 2024)
To understand the key processes of hydraulic fracturing in shale oil reservoirs, such as artificial fracture initiation and extension, proppant transportation and settlement, and the influencing factors of post-fracture production, many hydraulic fracturing field tests have been conducted in the United States. Examples include the ConocoPhillips tests and the National Hydraulic Fracturing Experiment. The results have promoted the innovation and development of fracturing technology. A good correlation exists between lithological changes and the roughness of artificial fractures. Although numerous artificial cracks are created, the number that can provide oil and gas seepage is relatively small, determined by the effectiveness of these cracks. The settlement of proppants in actual geological formations involves factors such as geology, lithology, fractures, and stress. The pressure data indicate that when the reservoir pressure drops below the bubble point pressure, the decline in production sharply increases. The key variables affecting shale oil well production include the horizontal well position, well spacing, horizontal section length, and sand addition intensity. These technologies are suitable for the adaptive process of China’s terrestrial shale oil fracturing, promoting the development and rapid increase of shale oil production.